Sixteen‐Week Physical Activity Intervention in Subjects With Increased Cardiometabolic Risk Shifts Innate Immune Function Towards a Less Proinflammatory State - Noz, Marlies P.; Hartman, Yvonne A. W.; Hopman, Maria T. E.; Willems, Peter H. G. M.; Tack, Cees J.; Joosten, Leo A. B.; Netea, Mihai G.; Thijssen, Dick H. J.; Riksen, Niels P. (Journal of the American Heart Association, 2019)
Background Low-grade inflammation, largely mediated by monocyte-derived macrophages, contributes to atherosclerosis. Sedentary behavior is associated with atherosclerosis and cardiovascular diseases (CVD). We examined whether reducing sedentary behavior and improving walking time improves monocyte inflammatory phenotype in subjects with increased cardiovascular risk. Methods and Results Across 2 waves, 16 individuals with increased cardiovascular risk performed a 16-week intervention study (age 64±6 years, body mass index 29.9±4.3 kg/m ), using a device with vibration feedback to promote physical activity. Before and after intervention, we objectively examined physical activity (ActivPAL), cytokine production capacity after ex vivo stimulation in peripheral blood mononuclear cells, metabolism of peripheral blood mononuclear cells, circulating cytokine concentrations, and monocyte immunophenotype. Overall, no significant increase in walking time was found (1.9±0.7 to 2.2±1.2 h/day, =0.07). However, strong, inverse correlations were observed between the change in walking time and the change in production of interleukin (IL)-1β, IL-6, IL-8, and IL-10 after lipopolysaccharide stimulation ( =-0.655, -0.844, -0.672, and -0.781, respectively, all <0.05). After intervention optimization based on feedback from wave 1, participants in wave 2 (n=8) showed an increase in walking time (2.2±0.8 to 3.0±1.3 h/day, =0.001) and attenuated cytokine production of IL-6, IL-8, and IL-10 (all <0.05). Glycolysis ( =0.08) and maximal OXPHOS ( =0.04) of peripheral blood mononuclear cells decreased after intervention. Lower IL-6 concentrations ( =0.06) and monocyte percentages ( <0.05), but no changes in monocyte subsets were found. Conclusions Successfully improving walking time shifts innate immune function towards a less proinflammatory state, characterized by a lower capacity to produce inflammatory cytokines, in individuals with increased cardiovascular risk. Clinical Trial Registration Information URL: http://www.trialregister.nl. Unique identifier: NTR6387.